Karkteristik Program Pembelajaran Pondok Pesantren Syifa’ul Qulub - Miftahul Janah; Norhikmah; Fahmi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research compares the characteristics and learning methods between Salafiyah Islamic boarding schools that focus on classical books and the understanding of Salafus Shalih, with modern or Khalafiyah Islamic boarding schools that integrate general and religious curricula. A case study at the Syifaul Qulub Islamic boarding school shows the adoption of the curriculum of the Darussalam Martapura Islamic boarding school with an emphasis on learning classical books through the sorogan and bandongan methods, reflecting a traditional approach in the educational process. Salafiyah Islamic boarding schools emphasize the study of classical religious sciences, while Khalafiyah Islamic boarding schools combine religious and general sciences. The main objective of Salafiyah Islamic boarding schools is to shape Muslim characters who are faithful, pious, and provide positive benefits to the community, although they do not formally state their objectives, but rather have an orientation to maintain the purity of Islamic teachings according to the understanding of Salafus Shalih. Salafiyah Islamic boarding schools play an important role in shaping the character and morals of the students, by instilling the values of discipline and Islamic ethics, while still adhering to traditional values and contributing to social activities and da'wah, making a significant contribution to Islamic education in Indonesia.